Desire for formal psychological support among caregivers of patients with cancer: prevalence and implications for screening their needs. Issue 6 (8th August 2012) - Merckaert, Isabelle; Libert, Yves; Lieutenant, Frédérique; Moucheux, Angélique; Farvacques, Christine; Slachmuylder, Jean‐Louis; Razavi, Darius
Abstract: Objective: To investigate the prevalence of desire for formal psychological support of primary caregivers of patients with cancer and to identify caregivers' and patients' socio‐demographic and psychological characteristics as well as patients' disease‐related characteristics associated with this desire. Methods: This is a multicenter, cross‐sectional study assessing desire for formal psychological support among consecutive primary caregivers of patients with cancer. Patients and caregivers completed the Hospital Anxiety and Depression Scale and reported their desire for formal psychological support. Results: Two‐hundred and eighty‐two patient–caregiver dyads were assessed. Forty percent of patients had breast cancer, 16% had a hematologic cancer, 12% had a gastrointestinal cancer, and 32% had another solid tumor. Nineteen percent of caregivers reported desiring formal support, and 54% experienced moderate to high levels of distress. Regression analysis showed that caregivers' desire for formal support was negatively associated with caregivers' age (Exp(B) = 0.95; p < 0.001 ) and education levels (Exp(B) = 0.35; p = 0.032 ) and positively with caregivers' level of distress (Exp(B) = 1.08; p < 0.001 ) and with patients' desire for formal psychological support (Exp(B) = 2.54; p = 0.008 ). These variables only predicted 25% of caregivers who desire formal support. Conclusions: One out of five caregivers desires formal psychological support although one out of two caregivers experiences significant levels of distress. The weak association between caregivers' desire for formal support and distress emphasizes the need to implement systematic screenings of both their distress and their desire for formal psychological support in oncology. Copyright © 2012 John Wiley & Sons, Ltd.